Don't fidget a feather! - Silverman, Erica; Schindler, S. D. (New York : Macmillan ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1994)
Their contest to decide who is the champion of champions almost has disastrous consequences for Gander and Duck.
Keywords: Competition (Psychology) -- Fiction; Ducks -- Fiction; Geese -- Fiction